Satisfaction of Patients with Type II Diabetes on Health Service in Specialized Center for Endocrinology and Diabetes /Baghdad 2019 - Kadium, Nazik L (AL-Kindy College Medical Journal, 2020)
Background: Patient satisfaction is of increasing importance and widely recognized as an important indicator of quality of the medical care. There was no homogeneous definition of patient satisfaction, since satisfaction concerns different aspects of care or settings, as well as care given by various professions. Objective: The objective of this study is to assess the patients’ level of satisfaction with diabetes care and to identify the underlying factors influencing it. Methods: This cross-sectional study had been conducted in the Specialized Center for Diabetes and Endocrinology in Baghdad Al- Rusafa 2018. Where150 type two diabetic patients attending their follow-up were requested to fill the questionnaire. The questionnaire identified patients, doctors, and practice related factors. For statistical analysis of the data, SPSS Version 24 was used, and the Chi-square statistical test was applied, A p-value less than 0.05 was considered statistically significant. Results: The study showed that the overall level of satisfaction was 79.3%. There was a statistically significant association between age group, gender, profession, educational level and marital status where P value 0.001 for all variables. Conclusion: It was concluded from the study that patients’ satisfaction was high. Majority of the diabetic patients were satisfied with health services, the level of satisfaction increases with age, female gender, and married patients, but it decreases with a high level of education and profession. High level of dissatisfaction seen on treatment services